Exploration of chemical compositions in different germplasm wolfberry using UPLC-MS/MS and evaluation of the in vitro anti-inflammatory activity of quercetin - Lan, Tian; Duan, Guozhen; Qi, Youchao; Almezgagi, Maged; Fan, Guanghui; Ma, Yonggui (Frontiers in Pharmacology, 2024)
Wolfberry, esteemed as a traditional Chinese medicinal material and functional food, is replete with nutrients and boasts a diverse array of health benefits, including hypoglycemic, antitumor, antioxidant, anti-inflammatory, and immune-enhancing properties. Notably, inflammation is a pivotal factor in the onset and progression of numerous diseases. Despite this, there is a paucity of research on the comprehensive evaluation of the components found in different wolfberries, and the exploration of their primary active components is limited. To address this issue, we conducted a comprehensive targeted metabolomics analysis, employing statistical methods such as principal component analysis (PCA), orthogonal partial least squares discriminant analysis (OPLS-DA), KEGG pathway analysis, and volcano plots to delineate the compositional differences among red, black, and yellow wolfberries. Furthermore, we investigated the anti-inflammatory effects of their primary components through in vitro experiments. Our analysis revealed a total of 1104 chemical compositions in the three wolfberries, with alkaloids, phenolic acids, flavonoids, and lipids being the predominant nutritional components. KEGG enrichment analysis indicated that these compositions were primarily involved in the biosynthesis of secondary metabolites, ABC transport, and galactose metabolism pathway. Moreover, our study demonstrated that quercetin exhibited dose-dependent anti-inflammatory activity in LPS-stimulated HUVECs. It effectively inhibited the production of inflammatory factors such as TNF-α, MCP-1, and IL-1β, while also down-regulating the gene and protein expression levels of ICAM-1 and VCAM-1. In conclusion, our findings indicate that there are variations in compositions among the three wolfberries, with flavonoids being the most abundant, and in vitro studies also confirmed the anti-inflammatory potential of quercetin. It is worth noting that L. ruthenicum contains higher levels of antioxidant components and possesses greater nutritional value, providing valuable insights for the future development and utilization of the three wolfberries.